UPAYA PEMERINTAH INDONESIA MENJADIKAN KAWASAN GUNUNG SEWU SEBAGAI UNESCO GLOBAL GEOPARK NETWORK(GGN) TAHUN 2013-2015 - Amelia, Deona Fhenta; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research is a study of contemporary which discussing about Indonesia efforts to make Gunung Sewu as Global Geopark Network of UNESCO from 2013 to 2015. Global Geopark Network is a network under the name of UNESCO who’s the role is to conduct geological heritage conservation and to promote sustainable development in society. UNESCO begin the program of Geopark in 1999 and cooperate with Gopark organization in Europe.In this research, the author uses the nation analysis level which focused on the efforts of Indonesia to make Gunung Sewu as Global Geopark Network.. This research uses a Neo-Realist perspective in international relations and Diplomacy theory of William C. Olson. Indonesia effort to make Gunung Sewu as Global Geopark Network is to submit all the dossier about Gunung Sewu that compatible with requirement from UNESCO.In effort to make Gunung Sewu as Global Geopark Network, Indonesia find the obstacle such as least the coordination and lack of active participation from local government. Gunung Sewu got rejected two times in efforts to be one of the Global Geopark Network.Keywords: Geological heritage, conservation, sustainable development, geopark, tourism, Gunung Sewu, Geodiversity, Biodiversity, Culturediversity.